Managing Occupational Stress - N. Wadesango; E. Gudyanga (Kamla Raj Enterprises (KRE), 2023)
The purpose of this desktop research study was to review literature on stress management by school heads. The article is based on secondary data collected through review of studies, reports and policy documents. Key issues investigated include definition of stress and occupational stress, sources of occupational stress, effects of occupational stress, strategies to counter or minimize the effects of occupational stress and conceptual framework of occupational stress. The study findings showed that consequences of physiological effects include blood pressure, diabetes, dizziness, ulcers, heart diseases and headaches. Physiological consequences include anxiety, frustrations, fatigue, tension, boredom, irritability, threatened, depressions, low self-esteem and feeling guilt and shame. Relaxations after work, change of school environment and inducement of drugs for temporary stress ‘escape’ experience were also suggested to minimize head teachers occupational stress. The study also recommended that there be clear definitions of workers roles and responsibilities for school head teachers.